The Penanaman Karakter Cinta Lingkungan pada Peserta Didik melalui Program Mini Garden - Elsafira, Defi Amalia; Jannah, Ana Naimatul (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
This research aims to analyze the cultivation of the character of love for the environment in students at SD Negeri Mlajah 2 Bangkalan through the "Mini Garden" program. The location of this research is at SD Negeri Mlajah 2 Bangkalan. The research method used in this research is descriptive qualitative with the data collection techniques used, namely observation and documentation. The subjects in this research were the researchers themselves who were assistant students at SD Negeri Malajah 2 Bangkalan and also students. The results of the research concluded that the "Mini Garden" Work Program at SD Negeri Mlajah 2 Bangkalan was successful in instilling the character of loving the environment in students. Through this activity, children not only learn about small farms, but also develop awareness of the importance of protecting the environment. By participating in planting and maintaining plants, they develop a sense of responsibility towards the natural environment. This program not only stimulates practical skills, but also creates positive values related to sustainability and care for the ecosystem.